Manajemen Biaya dan Waktu pada Pekerjaan Pembangunan Gedung Serba Guna Lontar Surabaya Menggunakan Metode CPM dan PERT - Rasio Hepiyanto; Rio Rahma Dhana; Galang Syahri Romadhon (Universitas Batanghari Jambi, 2026)
A project is an activity carried out to produce services that have a specific schedule. In the implementation of the project, there is a discrepancy between planning and realization, both in terms of time and cost. Scheduling is determined by the relationship of a project activity that is made very detailed and accurate. Especially in the construction of the Lontar Surabaya Multipurpose Building. The aim is to analyze to find out the processing of the application of the CPM (Critical Path Method) and PERT (Project Evaluation and Review Technique) methods. These two methods identify activities that affect project completion to predict costs, duration, critical paths and probabilities of a project. The research was conducted quantitatively by collecting primary and secondary data and through interviews with results in the field. The results of the research implementation show that the critical path in the project occurs in activities, A – B – H – I – J – K – M – N – F – E – O – O1 – O2 – O3 – G – Q – P – T – T1 – T2 – Z – Z1 – Z2 – Z3 – Z4 – Z5. Witg having a total duration of 79 days using the CPM and PERT methods, there were cost and time savings of 11 days.